Faktor-faktor Marketing Mix yang Berhubungan dengan Keputusan Pasien Memilih Rawat Inap Rumah Sakit Manembo-Nembo Bitung - Rickhard Williams Makawimbang; Grace Ester Caroline Korompis; Sylvia L Mandey (Universitas Sam Ratulangi, 2020)
Background: Hospital marketing management is an effort that can be done to make utilization of hospital services higher and thus impact on the decision of patient choosing a hospital, the high and low desire of consumers or the public to use a hospital service product based on the application of the existing marketing mix. Research Methods: This study was an observational study with a cross sectional study design. The population in this study were patients from all classes of hospital care. The sample in the study was a sample that met the inclusion and exclusion criteria of 53 patients. The variables in this study were the marketing mix variable, namely: location, cost, personnel, promotion, physical evidence, products with the dependent variable, namely the decision to choose hospitalization. The research data were analyzed using univariate, bivariate and multivariate analysis and logistic regression statistical calculations. Presentation of data was made in table and narrative form. The research data were analyzed using univariate, bivariate and multivariate analysis and logistic regression statistical calculations. Data presentation was made in the form of tables and narratives. Research Results: The results showed that there was a significant relationship between the location and the decision to choose hospitalization with a value of p = 0.004, there was a significant relationship between costs and the decision to choose hospitalization with a value of p = 0.000, there was a significant relationship between personnel and the decision to choose hospitalization with a value of p = 0,000, there was no significant relationship between promotion and the decision to choose hospitalization with a value of p = 0.184, there was a significant relationship between the process and the decision to choose hospitalization with a value of p = 0.018, there was a relationship between the product and the decision choosing hospitalization with a value of p = 0.013 and there was no significant relationship between physical evidence and the decision to choose to be hospitalized with a value of p = 0.300. The results of the multivariate analysis showed that cost (p = 0.001) was the most dominant factor influencing the decision to choose to be hospitalized at Manembo-nembo Type C Hospital. Conclusion: The conclusion of this study is that the factors of location, cost, personnel, processes and products are related to the decision to choose to be hospitalized. The most dominant factor related to the decision to choose to hospitalization is cost.